Odpowiedzi

Najlepsza Odpowiedź!
2010-02-14T15:09:58+01:00
X2 = (√65)2 + (x-5)2
X2 = 65 + (x-5) (x-5)
X2 = 65 + x2 – 5x – 5x + 25
X2 - X2 +5x +5x = 65 +25
10x = 90 / :10
X = 9

9 - 5 = 4


Obw. = 4 + 9 +√65 = 13+ √65
P=(4×√65)/2=2√65
1 5 1
2010-02-14T15:17:44+01:00
√65 -pierwsza przyprostokątna
x-5 - druga przyprostokątna =4
x -przeciw prostokątna =9

(√65)²+(x-5)²=x²
65+x²-10x+25=x²
90+x²-10x=x²
90=10x
x=9

9-5=4 druga przyprostokatna

P=a*h/2
P=√65*4/2=√65*2 [cm]²
Obw=√65cm+9cm+4cm=√65+13cm
1 5 1